Análise instrumental de uma maquete tátil para a aprendizagem de probabilidade por alunos cegos - Vita, Aida Carvalho (2012)
This thesis aimed to identify the potential of didactic material (DM), the tactile-type model, for blind students' learning of basic concepts of Probability (bcP). The qualitative research investigated the design, construction and evaluation of MD and for this purpose we proceeded with the curricular adaptations necessary to meet the established objective. The theoretical framework was derived from cognitive ergonomics, particularly the Rabardel instrumental approach. The model was constructed as sequence from five prototypes (M1, M2, M3, M4, M5). Each followed the five steps of user-centred design (UCD) methodology. The relations among the four poles of the collective activities of instrumented situations (CAIS) model, adapted from Rabardel s model, were used as an instrumental analysis of each prototype's. There were poles of this model: blind student (S), tactile model (I), bcP (O) researchers/specialists (P). After conclusion of the analysis, M5 was validated as the (I) of this thesis for learning bcP by blind students. This, in turn, was composed of a board, two hundred and forty letters EVA terry and flat, seven hives, three hundred toys, a stroller, two plastic covers (terry and flat) to sort and tasks. The participants were four students with acquired blindness, one from Sao Paulo and three from Bahia. The investigation of the model's capability was based on the concept of usability, i.e. effectiveness, efficiency and satisfaction, in accordance with Nielsen's design principles. The bcP were approached from the perspective of the probabilistic literacy model proposed by Gal to solve a sequence of tasks in the situation known as Jefferson's random walks. The model has the potential to be used as a DM in the educational environment, especially in learning bcP. It was considered to be an efficient tool for moulding curricular adaptations to meet the needs of blind students in solving tasks. It was also considered effective for presenting a configuration that allowed experienced students or beginners to develop similar strategies for solving the tasks, demonstrating skills and increasing speed of movement on the board and records in hives. The physical arrangement of the model, with its aesthetic and minimalist design, showed a level of usability adequate to meet the students' needs. Finally, the model proved to be an MD compatible with the physical characteristics of the students, who used touch to gather information and said they were satisfied with the model. Moreover, it seemed to be in accordance with the predetermined dimensions of efficiency, effectiveness and satisfaction in terms of learning bcP. It enabled the students, for example, to demonstrate competence and proficiency in the random experiment and the construction of pictograms. Regarding limitations encountered, the MD did not allow students to act with autonomy during the experiment. To minimize this limitation, the researcher played the role of facilitator between the MD, the student and the bcP. It is hoped that this DM will contribute to inclusive education, even though its presence in the classroom does not guarantee by itself the learning of bcP